Effect of preannealing on the morphology of LiTaO3 thin films prepared from the polymeric precursor method - Gonzalez, AHM; Simoes, A. Z.; Zaghete, M. A.; Varela, José Arana [UNESP] (Elsevier B.V., 2003)
Lithium tantalate (LiTaO3) thin films with 50:50 stoichiometry were deposited on silicon (100) substrates with two layers by the spin coating method using a polymeric organic solution. In order to study the influence of preannealing on the crystallinity, microstructure, grain size and roughness of the final film, two annealing procedures, slow preannealing and fast preannealing, were used. X-ray diffraction (XRD) results showed that LiTaO3 thin films are polycrystalline. It was observed by scanning electron microscopy (SEM) that the thin film, which had been thermally treated using slow preannealing, was characterized by a dense and homogeneous surface. The atomic force microscopy (AFM) studies showed that the roughness is strongly influenced by preannealing temperature. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: LiTaO3; thin films; polymeric precursor